PENGARUH BRAND IMAGE, PRICE PERCEPTION, DAN SERVICE QUALITY TERHADAP KEPUTUSAN PEMBELIAN PADA CITRA KENDEDES CAKE & BAKERY Jl. MT. Haryono No 73 Malang - Nurul Latifah; Rois Arifin; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT Bussiness development in economic side become more competitive. Facing the competition a company  must be able to read and optimalize the economical resources to increase competitive ther product, be able to set the effective marketing strategy, and alwayscontinuing to develop its strategy. This study aim at analying the effect of brand image, price perception, and service quality toward buying decision at Citra Kendedes Cake & Bakery Jl. MT. Haryono No 173 Malang. the popolation was the consumer of Citra Kendedes Cake & Bakery. Accidental sampling technique were use. While its based on the coming consumer when the research were conducted. The sample were 82 respondents. The data were analyzed using  multiple linier regression method. The result showed (1) brand image has positive influnce and significant on buying decision. (2) price perception has positive influence and significant on buying decision. (3) service quality has positive influence and significant on buying decision. Keyword : Brand Image, Price Perception, Service Quality, and Buying Decision